KAJIAN IMPLEMENTASI PEMBELAJARAN IPS TERPADU DALAM MEMBENTUK SIKAP TOLERANSI MULTIKULTURAL SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is a country with diverse ethnicities, religions, and cultures, making it crucial to instill an attitude of tolerance from an early age through education. This study aims to analyze the implementation of integrated social studies learning based on multicultural values ​​in shaping students' attitudes of tolerance. This study used a qualitative approach with a literature review method of relevant scientific articles from 2016–2026. Data was obtained from Google Scholar and Garuda, then analyzed using content analysis techniques. The results showed that multicultural-based social studies learning was able to significantly increase attitudes of tolerance, empathy, and appreciation for diversity. Learning strategies such as group discussions, project-based learning, and collaborative models proved effective in integrating multicultural values. However, there are still obstacles such as limited teacher understanding, lack of learning innovation, and a lack of relevant teaching materials. Therefore, it is necessary to improve teacher competence and develop contextual learning so that the implementation of multicultural education can run optimally in shaping students' attitudes of tolerance.